Parental Education and Gadget Knowledge: Their Impact on Gadget Use Behavior in Children Aged 5-6 Years - Andika Sari, Diah; Damayanti, Anita; Bahfen, Munifah; Zulhaini, Luthfia (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2024)
This study investigates the relationship between parental education levels, gadget knowledge, and the gadget use behavior of children aged 5-6 years. Using a quantitative correlational research methodology, data were collected via a structured questionnaire from 168 parents across Indonesia. The questionnaire assessed parental education, knowledge of gadget use, and children's gadget use behavior. Results showed no significant correlation between parents' education levels and children's gadget use behavior. However, a low positive correlation was identified between parents' gadget knowledge and children's gadget use behavior. This suggests that parents with higher gadget knowledge can more effectively manage their children's gadget use. This finding underscores the importance of enhancing parental understanding of digital technology to foster healthier gadget use among young children. Limitations of the study include reliance on self-reported data and a predominantly maternal sample, which may only partially represent the broader population. Additionally, the cross-sectional nature of the study limits the ability to conclude long-term effects. Future research should involve more diverse samples, consider additional variables such as socio-economic status and cultural factors, and employ longitudinal designs to explore the long-term impacts of parental gadget knowledge on children's development. These steps are essential to gain a more comprehensive understanding of the factors influencing children's gadget use behavior and to inform strategies aimed at promoting healthier digital habits among young children.